Suicide Prevention At Schools. The Project "+Contigo" - Santos, José Carlos Pereira dos (2013)
INTRODUCTION AND AIMS: According to the National Mental Health Plan, the prevention of suicidal behaviors among adolescents is now one of the priority intervention areas in Portugal. Adolescent depression is a leading cause of morbidity and mortality, associated with difficulties in family relationships and social life, impaired academic performance, and increased risk for substance abuse and suicide. Epidemiological studies show that the prevalence of adolescent depression varies between 3% and 9%, with a cumulative prevalence of 20% by the end of the teenage years. However, despite available depression treatments, only about 25% of depressed youth receive treatment and at least 20% develop recurrent, persistent, and chronic depression. The purpose of this study was to assess the presence and severity of depressive symptoms, coping and self-concept in a nonclinical population of adolescents. It aims to improve coping and self-concept, detect depression symptomatology, and fight against stigma in order to implement a school-based Suicide Prevention Plan. METHODS: The Project "+Contigo" was developed by the authors to prevent suicidal behaviors among adolescents. The first step is a screening using the Portuguese version of BDI-II, Self-Concept Scale 2, Coping Scale and WHO-Five Well-Being Index. It was self-administered to 741 adolescents aged between 11 and 18 years from secondary education institutions in the Centre Region of Portugal. Then we had four moments in the classroom to discuss adolescence, mental health, risk behaviors and how to improve well-being, coping skills and self-esteem. The impact of the intervention was assessed one week and six months later. RESULTS: 31.2% of adolescents experience depression and 17.7% of these have moderate to severe depressive symptoms. Girls are more depressed than boys (p<0.001). After the intervention, adolescents reduced depression, and improved coping skills, self-concept and well-being. In the six-month follow-up, the results remained satisfactory, mainly in terms of depression and well-being. CONCLUSIONS: Due to the high prevalence of depression and its strong association with suicidal behaviors, school-based prevention strategies ought to be designed: mental health promotion by fighting against stigma; promotion of self-esteem and problem-solving skills; health education on depressive symptoms and risk behaviors (for teachers, parents and students); early detection, referral and adequate treatment